Psychology in Latin America: Legacies and Contributions. Part 3 - Consoli, Andres J. (2015)
The purpose of this series is to advance the dissemination of psychological knowledge generated in Latin America and the Caribbean in an effort to balance the predominant influence and presence of European psychology and, more recently, Asian psychology, in the U.S.A. This is the third and final part of a series discussing the Interamerican Society of Psychology (www.sipsych.org), known as SIP (for the acronym of its name in Spanish, Sociedad Interamericana de Psicología) and featuring the Spanish or Portuguese speaking psychologists distinguished with the Interamerican Psychology Award. Every two years, SIP’s board of directors, in consultation with nominations from SIP’s membership, grants an award to an English or French speaking psychologist and another to a Spanish or Portuguese speaking psychologist1 whose work has advanced psychology as a science and profession in the Americas.